Decorative Motifs on the Woven Cloth: Local and Indonesian Fine Arts Education Study - Jayadi, Jayadi; Ahmad, Abd. Aziz; Yunus, Pangeran Paita (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study aims to analyze the meaning of motifs, functions of motifs, and functions of bebet woven fabrics in the Sasak Ende community in terms of education and economy. This study uses a qualitative approach with an ethnographic approach, in-depth interviews, and documentation. We conducted this study in the Sasak Ende Tourism Village, Central Lombok Regency. Data analysis was carried out in the stages of data reduction, data presentation, and drawing conclusions. The results of the study showed that the kembang komak putiq woven cloth (white komak bean motif) is one of the oldest woven cloths with geometric patterns in the form of vertical lines and horizontal lines, forming a checkered motif that has been woven from generation to generation, Selentang (animal feet, Ragi bararti bumbu Bingkal means